2023
DOI: 10.2355/isijinternational.isijint-2022-321
|View full text |Cite
|
Sign up to set email alerts
|

Decarburization Kinetics of Fe–C Melt with CO<sub>2</sub>–O<sub>2</sub> Mixed Gas by Isotope Tracing Method

Abstract: The partial substitution of O 2 with CO 2 in steelmaking process is an important technology to reduce CO 2 emission and recycle. In order to improve CO 2 -O 2 decarburization utilization, the decarburization kinetics of Fe-C melt with CO 2 -O 2 mixed gas have been studied using 13 CO 2 -18 O 2 dual isotope tracing method and established the decarburization kinetic model. The results show that less than 40% of the oxygen is partially replaced by CO 2 , which improves the O 2 utilization involved in the decarbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…13 CO 2 -18 O 2 Dual Isotope Tracing Mechanism Using 13 CO 2 -18 O 2 dual isotope gases, the mixed gas complex reactions can be distinguished clearly in the impact zone of the cavity: I. Reactions between mixed gas and carbon on the molten surface Based on the previous work, 10) it was assumed that Q x1 , Q x2 and Q x3 (mL•min − 1 ) were the flowrates of uninvolved reaction, CO 2 formed by carbon and oxygen, and CO 2 from post combustion; Q y1 , Q y2 , Q y3 and Q y4 (mL•min − 1 ) were the O 2 consumption to form CO 2 , the O 2 consumption to form CO, the O 2 consumption to post combustion, and the O 2 uninvolved reaction; Q z1 , Q z2 and Q z3 (mL•min − 1 ) were the CO product from O 2 , the CO product from CO 2 , and the CO consumption to post combustion, respectively; Q α and Q β were the inlet gas flowrates of CO 2 and O 2 ; Q total was the overall flowrates at outlet. As for the ion currents monitored by mass spectrometer, I 28 , I 29 and I 30 were ion currents of 12…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…13 CO 2 -18 O 2 Dual Isotope Tracing Mechanism Using 13 CO 2 -18 O 2 dual isotope gases, the mixed gas complex reactions can be distinguished clearly in the impact zone of the cavity: I. Reactions between mixed gas and carbon on the molten surface Based on the previous work, 10) it was assumed that Q x1 , Q x2 and Q x3 (mL•min − 1 ) were the flowrates of uninvolved reaction, CO 2 formed by carbon and oxygen, and CO 2 from post combustion; Q y1 , Q y2 , Q y3 and Q y4 (mL•min − 1 ) were the O 2 consumption to form CO 2 , the O 2 consumption to form CO, the O 2 consumption to post combustion, and the O 2 uninvolved reaction; Q z1 , Q z2 and Q z3 (mL•min − 1 ) were the CO product from O 2 , the CO product from CO 2 , and the CO consumption to post combustion, respectively; Q α and Q β were the inlet gas flowrates of CO 2 and O 2 ; Q total was the overall flowrates at outlet. As for the ion currents monitored by mass spectrometer, I 28 , I 29 and I 30 were ion currents of 12…”
Section: 2mentioning
confidence: 99%
“…In our previous works, [8][9][10] using 13 CO 2 -18 O 2 dual isotope gases, the mixed gas complex reactions can be distinguished clearly in gas-liquid reaction interface. On the basis, the change of gas concentration in the cavity was studied by changing the injection height, and the influence of post combustion on decarburization process was also analyzed.…”
Section: Introductionmentioning
confidence: 95%
“…Carbon monoxide does not appear as reactant in the considered chemical reactions seen in Eqs. [1] to [4].…”
Section: Model Descriptionmentioning
confidence: 99%
“…The reaction-controlled mechanism was disregarded as it was found that hot spot temperatures can exceed well over 2000 °C [11] and even at lower temperatures, these phenomena play a subservient role. [1] The total species transport to the hot spot is proportional to the area of the cavity (calculated using the model of Koria [12] ), and the specific species transport through the gaseous boundary layer (using Eq. [5]).…”
Section: Model Introductionmentioning
confidence: 99%
See 1 more Smart Citation